Striking Features of Andaman Forestry - Chaudhry, Pradeep (Indian Forester, 1998)
The paper deals with certain unique features of timber harvesting operations in Andaman group of Islands and its related consequences on fragile ecosystem of these Islands. An integrated approach involving improvement in land use pattern, cattle-management, local people - Industry - Administration interface has been stressed upon.